Antioxidant effect of Spinach on Intra-testicular Testosterone levels in Obese Rats - Iqbal, Somia; Ali, Shazia; Siddiqui, Arif (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Objective: To determine the antioxidant effects of spinach on Intra-testicular testosterone levels and histopathological changes in testicular tissue in obese Sprague Dawley rats. Methodology: It was an experimental, randomized control trail, performed at multidisciplinary research laboratory of Islamic International Medical College, Rawalpindi and Animal House at National Institute of Health (NIH), Islamabad, Pakistan from April 2016 to March 2017. In this study, 40 male Sprague Dawley rats were randomly allocated into control(Group-A) and Experimental groups. For duration of six weeks, control group was fed on standard diet while experimental group was fed on high fat diet to induce obesity. Afterwards, experimental group was divided into Group B-Obesity control group and Group C-Spinach treated group. Intra-testicular testosterone levels and testicular tissue histology of Group A and Group B rats were evaluated. Afterward 5% spinach hot water extract along with high fat diet was given to Group C for four weeks and finally Intra-testicular testosterone levels and testicular tissue histology were measured in this group. Results: Intra-testicular testosterone levels of Group B rats was significantly decreased (P<0.001) as compared to Group A rats. However, Intra-testicular testosterone levelsof Group C rats was significantly increased (P<0.001) as compared to Group B rats after spinach administration. Testicular tissue histology of Group A ratsshowed normal shaped seminiferous tubules with eight to nine layers of spermatogenetic cells, while atrophic seminiferous tubules with five to six layers of spermatogenetic cells were observed in Group B rats. However administration of spinach in Group C rats showed seminiferous tubules with increased number of mature spermatozoa in their lumen and eight to nine layers of spermatogenetic cells. Conclusion: Spinach has restorative effects on male reproductive system by normalizing the intra-testicular testosterone levelsand by restoring the structure of testicular tissuesin response to obesity-induced oxidative stress. Key word: Antioxidant, Intra-testicular testosterone, Obesity, Spinach